Odpowiedzi

2010-03-09T17:09:11+01:00
Rozzwiaz równania
3x=2x+1/7
3x-2x=1/7
x=1/7

3-x=-2x
-x+2x=-3
x=-3
spr.
L=3-(-3)=6
P=-2(-3)=6
L=P

5y=13
y=13:5
y=2,6

1/7 x=-2
x=-2*7
x=-14

-7b=7/8
b=7/8:(-7)
b=-1/8

7x+7=35
7x=35-7
7x=28
x=28:7
x=4

2-x=5-2x
-x+2x=5-2
x=3

69-x=x+96
x+x=69-96
2x=-27
x=-13,5

1/2 x +5=x +8
x-1/2 x=5-8
1/2 x=-3
x=-3*2
x=-6
2010-03-09T17:39:04+01:00
3x = 2x+1/7
3x-2x = 1/7
x = 1/7

spr.:
L = 3*1/7 = 3/7
P = 2*1/7+1/7 = 2/7+1/7 = 3/7
L = P


3-x = -2x
-x+2x = -3
x = -3

spr.:
L = 3-(-3) = 6
P = -2*-3 = 6
L = P


następne sprawdzenia na tej samej zasadzie


5y = 13 |:5
y = 2,6


1/7x = -2 |:1/7
x = -14


-7b = 7/8 |:(-7)
b = -1/8


7x+7 = 35
7x = 28 |:7
x = 4


2-x = 5-2x
-x+2x = 5-2
x = 3


69-x = x+96
-x-x = 96-69
-2x = 27 |:(-2)
x = -13,5


0,5x+5 = x+8
0,5x-x = 8-5
-0,5x = 3 |:(-0,5)
x = -6
2010-03-09T17:56:43+01:00
A)3x=2x + jedna siódma | - 2x
x=jedna siódma
b)3-x=-2x ----> odwracamy kolejność
-2x=3-x | +x
-x=3 | * -1
x=-3
c) 5y=13 |:5
y=2,6
d) jedna siódma x=-2 | *7
x=-14
e)-7b=siedem ósmych | : -7
b= - jedna ósma
f)7x+7=35 |-7
7x=28 | :7
x=4
g) 2-x=5-2x | +2x
2+x=5 |-2
x=3
h)69-x=x+96 |+x
69=2x+96
2x=96+69
2x=165 |:2
x=82,5
i)jedna druga x+5=x+8 |*2x
x+5=2x+8 |-5
x=2x+3 |*2x
2x=4x+3 |-4x
-2x=3 |*-2
x=-6